2018
DOI: 10.1016/j.chest.2018.08.1026
|View full text |Cite
|
Sign up to set email alerts
|

Standard Bronchoscopy With Fluoroscopy vs Thin Bronchoscopy and Radial Endobronchial Ultrasound for Biopsy of Pulmonary Lesions

Abstract: Bronchoscopy with or without a thin scope and R-EBUS had a poor diagnostic yield for pulmonary lesions. Future work should focus on improvements in technique and technology advances that ensure a higher likelihood of obtaining a diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
90
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(95 citation statements)
references
References 11 publications
3
90
1
1
Order By: Relevance
“…While not necessarily a study evaluating navigational bronchoscopy, Tanner et al . in their randomized trial comparing conventional bronchoscopy in conjunction with fluoroscopy versus conventional bronchoscopy with fluoroscopic guidance plus rEBUS provided useful information on these bronchoscopic interventions . Disappointingly, they reported a diagnostic yield ranging from 38% to 49%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While not necessarily a study evaluating navigational bronchoscopy, Tanner et al . in their randomized trial comparing conventional bronchoscopy in conjunction with fluoroscopy versus conventional bronchoscopy with fluoroscopic guidance plus rEBUS provided useful information on these bronchoscopic interventions . Disappointingly, they reported a diagnostic yield ranging from 38% to 49%.…”
Section: Discussionmentioning
confidence: 99%
“…The reported sensitivity of CT‐guided biopsy is 90%, but estimates for lesions <1.5 cm are less optimistic (70–82%) . In comparison, the overall diagnostic yield of currently available electromagnetic navigation bronchoscopy (ENB) techniques is lower, approaching 70–73% while other data suggest an even lower rate of 44–57% . When analysed more closely, the diagnostic yield appears to be influenced by nodule size and presence of a bronchus sign …”
Section: Introductionmentioning
confidence: 98%
“…Recently, a multicenter prospective study compared the diagnostic yield of standard TBB with that of R‐EBUS‐TBB and reported poor diagnostic yield despite combining R‐EBUS with standard TBB. This result may be explained by a high proportion of benign diseases among this study cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Although the lower complication profile of RP‐EBUS is appealing, its diagnostic yield did not exceed that of transthoracic needle biopsy. While one meta‐analysis reported a pooled diagnostic yield of >70% for RP‐EBUS, several reports showed much lower yields of RP‐EBUS: analysis of the ACCP Quality Improvement Registry, Evaluation, and Education (AQuIRE) registry reported a diagnostic yield of 57% for RP‐EBUS alone, whereas a multicentre prospective trial showed a yield of 49% in a group using thin bronchoscopes and RP‐EBUS …”
Section: Introductionmentioning
confidence: 99%
“…While one meta-analysis reported a pooled diagnostic yield of >70% for RP-EBUS, 8 several reports showed much lower yields of RP-EBUS: analysis of the ACCP Quality Improvement Registry, Evaluation, and Education (AQuIRE) registry reported a diagnostic yield of 57% for RP-EBUS alone, 9 whereas a multicentre prospective trial showed a yield of 49% in a group using thin bronchoscopes and RP-EBUS. 10 EBUS image analysis could be a good supporting technique for tissue sampling from the most suspicious lesion during diagnostic bronchoscopy. When the bronchoscopist encounters suspicious lesions in imaging assessments, the clinician can focus on repeated sampling from the targeted lesion.…”
Section: Introductionmentioning
confidence: 99%